What Is a Reference Source?. Issue 1 (2nd January 2019) - Roy, Loriene
ABSTRACT: Reference is the balance of employing a process to use materials to locate information. A key feature of teaching reference is to help students understand what a reference source is. This column introduces the dilemma of that seemingly easy task. It includes examples of course assignments to aid in that effort.